Manejo comunitario de la enfermedad diarreica aguda en niños menores de 5 años de edad del subcentro de salud rayito de luz de la ciudad de Machala, primer trimestre. Año 2014. - Romero Feijoo, Mishell (2015)
In Canton Machala for the year 2013 1185 cases of acute diarrheal disease were presented, during the first quarter of the same year, they recorded 198 cases in Subcentro Health Rayito de Luz. 2014 in the first quarter recorded 297 cases. Denoting the size rather than the number of cases but by the complications of this disease taking itself as sample for this study to 167 users. Diarrhea in the first year of life may impair nutritional status and cause serious consequences.